1997
DOI: 10.1093/clind/24.4.584
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Significance of Positive Blood Cultures in the 1990s: A Prospective Comprehensive Evaluation of the Microbiology, Epidemiology, and Outcome of Bacteremia and Fungemia in Adults

Abstract: To assess changes since the mid-1970s, we reviewed 843 episodes of positive blood cultures in 707 patients with septicemia. The five most common pathogens were Staphylococcus aureus, Escherichia coli, coagulase-negative staphylococci (CNS), Klebsiella pneumoniae, and Enterococcus species. Although CNS were isolated most often, only 12.4% were clinically significant. Half of all episodes were nosocomial, and a quarter had no recognized source. Leading identifiable sources included intravenous catheters, the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

40
662
14
59

Year Published

1999
1999
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 1,061 publications
(775 citation statements)
references
References 74 publications
40
662
14
59
Order By: Relevance
“…Thus, information on the prognosis of these five patients who received no antifungal treatment in the preintervention group is important. Moreover, assessing the clinical significance of candidemia, as in a previous study,2 would help to interpret the results of this study. Finally, the initial sentence in the Primary Outcome section of the Results is incorrect.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…Thus, information on the prognosis of these five patients who received no antifungal treatment in the preintervention group is important. Moreover, assessing the clinical significance of candidemia, as in a previous study,2 would help to interpret the results of this study. Finally, the initial sentence in the Primary Outcome section of the Results is incorrect.…”
mentioning
confidence: 82%
“…If these five patients survived at discharge without antifungal treatment, five (16.7%) of 30 patients with candidemia were considered not to have true candidemia that required treatment. This means that the clinical judgment not to treat for candidemia in these patients was appropriate, although most candida isolated from positive blood cultures reflects true candidemia 2. However, given that no gold standard exists for differentiating pathogens from contaminants,3 it is interesting that 16.7% of patients with candidemia were managed without any antifungal treatment.…”
mentioning
confidence: 99%
“…If only 1 set of blood cultures was acquired and was positive for a pathogenic organism (such as enteric Gram-negative bacilli or Streptococcus pneumonia) that could account for the clinical presentation, then the culture was considered positive. 7,14,15 Definition of Contamination We considered as contaminants organisms common to skin flora, including Bacillus species, coagulase-negative staphylococci, Corynebacterium species, and Micrococcus species, without isolation of an identical organism with the same antibiotic susceptibilities from another potentially infected site in a patient with incompatible clinical features and no attributable risks. 16 Single blood cultures positive for organisms thought unlikely to explain the patient's symptoms were also considered contaminants.…”
Section: Definition Of Bacteremiamentioning
confidence: 99%
“…6 Positive blood cultures can demonstrate not only an infectious cause of disease but also the microbiological response to antibiotic therapy. 7 However, studies have reported that 35% to 50% of positive blood cultures are falsely positive owing to contamination. [7][8][9][10][11] False-positive cultures may lead to the use of inappropriate or unnecessary antibiotics, additional testing and consultation, and prolonged hospitalizations that increase patient care costs.…”
mentioning
confidence: 99%
See 1 more Smart Citation